1999
DOI: 10.1097/00000441-199911000-00004
|View full text |Cite
|
Sign up to set email alerts
|

Vaccination against Hepatitis B in Patients with Chronic Liver Disease Awaiting Liver Transplantation

Abstract: Although the response rate to double-dose recombinant vaccines is higher than the previously reported response to single-dose vaccine, it still is less than optimal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
52
0
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 16 publications
2
52
0
4
Order By: Relevance
“…Pre-LT vaccination to provide endogenous anti-HBs is unlikely to be successful in the vast majority of patients. A recent North American study demonstrated only 37% response rate to double-dose hepatitis B vaccine in cirrhotics without history of hepatitis B infection (18). This contradicts data from some Asian studies, though the higher seroconversion rates in Asia may correlate with a higher underlying prevalence of HBV exposure (40).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Pre-LT vaccination to provide endogenous anti-HBs is unlikely to be successful in the vast majority of patients. A recent North American study demonstrated only 37% response rate to double-dose hepatitis B vaccine in cirrhotics without history of hepatitis B infection (18). This contradicts data from some Asian studies, though the higher seroconversion rates in Asia may correlate with a higher underlying prevalence of HBV exposure (40).…”
Section: Discussionmentioning
confidence: 96%
“…This mutant could be preexisting in the donor graft or potentially induced by HBIg prophylaxis or lamivudine therapy as has been previously described (16,17). The loss of protective anti-HBs serologies after known response to vaccination has been reported to range from 27% to 34% in studies with 3 years of follow-up (18)(19)(20)(21). In addition, loss of antiHBs is not uncommon following LT, even in patients with previous HBV exposure.…”
Section: Discussionmentioning
confidence: 99%
“…It is also clinically well recognized that cirrhotic patients have suboptimal responses to vaccines such as the hepatitis B vaccine. In several series, HBV vaccinations in cirrhotic patients yielded response rates from 13 to 54% [28,29] with minimal improvement by doubling the dose [30], much poorer than the results in noncirrhotic patients. In a study of conjugated pneumococcal vaccine in liver disease, cirrhotic patients showed transient exaggerated early IgM and IgA production but impaired total IgG response suggesting defective IgG class-switching among cirrhotic patients relative to healthy donors [31].…”
Section: Discussionmentioning
confidence: 99%
“…Tampoco se observa un incremento en los valores plasmáticos basales elevados de FNT-α con la vacuna. La tasa de seroconversión en pacientes con cirrosis es inferior y no supera el 16 ó 37% según se utilice una dosis estándar o una doble dosis en el esquema 47 .…”
Section: Diagnóstico Manejo Y Prevención De Infecciones En Pacientesunclassified